Preparation of Wyoming bentonite nanoparticles. Issue 5 (15th February 2016) - Sarkar, Grytan; Dey, Ashish; Siddiqua, Sumi
Abstract : Wyoming bentonite having a higher percentage of montmorillonite content shows a high swelling capacity, which enables it to seal itself when saturated, and it is widely used as a construction material of clay barrier system. The main goal of clay barriers is to seal the containment system from liquid intrusion, which could be assessed by the hydraulic conductivity of the barrier materials. The nanoparticles of the bentonite could be used to reduce the hydraulic conductivity. In this study, both the mechanical attrition and the synthesis process were assimilated to prepare nanoparticles of Wyoming bentonite. In the mechanical attrition process, the particles were ground in wet condition using planetary ball mill. Different parameters including types and size of balls, types of solvent, time period and speed of pulverisation for grinding were selected through continuous particle size analysis using the Zetasizer. The finer particles were synthesised using ultrasonication, centrifuging and filtering techniques. The particle size and the chemical composition of the dry particles were confirmed through scanning electron microscopy and energy-dispersive X-ray spectroscopy. In addition, the mineralogical change of the bentonite samples after the grinding process was observed using X-ray powder diffraction analysis. Finally, a particle size range between 30 and 100 nm was confirmed for the Wyoming bentonite nanoparticles.